2010
DOI: 10.1016/j.ijrobp.2010.01.028
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of G2-Phase Enrichment and Checkpoint Abrogation on Low-Dose Hyper-Radiosensitivity

Abstract: Purpose An association between low-dose hyper-radiosensitivity (HRS) and the “early” G2/M checkpoint has been established. An improved molecular understanding of the temporal dynamics of this relationship is needed before clinical translation can be considered. This study was conducted to characterize the dose response of the early G2/M checkpoint and then determine whether low-dose radiation sensitivity could be increased by synchronization or chemical inhibition of the cell cycle. Methods and Materials Two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
54
0
4

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 73 publications
(64 citation statements)
references
References 29 publications
6
54
0
4
Order By: Relevance
“…The DNA is the principal cellular target of ionizing radiation and the molecular mechanisms involved in the effect of radiation on the cell is complex. Series of molecular events take place after irradiation to the cell [13][14][15]. As a response of radiation induced damage, Ionizing Radiation Induced Factor (IRIF), a histone (H2AX) based protein complex is formed at the damaged site of the DNA.…”
Section: Discussionmentioning
confidence: 99%
“…The DNA is the principal cellular target of ionizing radiation and the molecular mechanisms involved in the effect of radiation on the cell is complex. Series of molecular events take place after irradiation to the cell [13][14][15]. As a response of radiation induced damage, Ionizing Radiation Induced Factor (IRIF), a histone (H2AX) based protein complex is formed at the damaged site of the DNA.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note that LDHRS has not been observed for high-linearenergy-transfer radiations (such as neutrons) [2,16], and this indicates that reparation plays an important role. It has also been suggested that the repair induction is a consequence of the fact that the cell cycle is stopped in the G2 phase, because this permits the cell to repair the lesions produced before it divides, and this only occurs for a given threshold dose [18][19][20]. According to several authors [21][22][23], this links LDHRS with the so-called dose rate inverse effect [24,25].…”
mentioning
confidence: 99%
“…This inhibition of xenografted tumor may result from direct cytotoxic ability of the radioisotope, significant injury to B-cell lymphocytes and natural killer cells or, possibly, the welldocumented phenomenon of low-dose radiation hypersensitivity. 10 Hematoxylin and eosin staining of sections of the xenografted tumors showed no immune cells present in tumors from mice that received the highest doses of [ 32 P]ATP, while the small, disrupted tumors examined from mice receiving optimal [ 32 P]ATP doses did contain infiltrating immune cells (data not shown).…”
mentioning
confidence: 90%